Ovarian Tumor Targeting of Docetaxel-Loaded Liposomes Mediated by Luteinizing Hormone-Releasing Hormone Analogues - Qin, Yao; Song, Qing-Guo; Zhang, Zhi-Rong; Liu, Jie; Fu, Yao; He, Qin; Liu, Ji (Arzneimittelforschung, 2008)
Recent studies indicate that luteinizing hormone-releasing hormone (LHRH) analogues (LHRHa), like LHRH, are able to specifically bind to LHRH receptors which are highly expressed on the extracellular membrane of ovarian tumor cells. As a targeting moiety, LHRHa can mediate the ovarian tumor targeting of docetaxel-loaded liposomes. In our study, synthesized negatively charged cholesterol succinimide (CHS) was employed for the preparation of negatively charged docetaxel-loaded liposomes, with which the positively charged LHRHa is linked via electrostatic absorption. An HPLC-based assay for determination of docetaxel (CAS 114977-28-5, Doc) in vivo and the model of ovarian cancer xenograft were established to investigat the biodistribution of docetaxel, docetaxel liposomes (Doc-Lipo), and LHRHa mediated docetaxel-loaded liposomes (LHRHa-Doc-Lipo) in nude mice. Sixty minutes after administration of LHRHa-Doc-Lipo, the concentration of docetaxel in the ovarian tumor was 2.86 times that of Doc-Lipo and 9.02 times that of Doc in the nude mice bearing ovarian tumor. LHRHa-Doc-Lipo decreased the concentration of docetaxel in the liver and spleen by 57% and 34%, respectively, as compared with Doc-Lipo. Therefore, LHRHa-Doc-Lipo exhibits potentiality as an active targeting drug delivery system for chemotherapy of ovarian tumor.
Keywords: CAS 114977-28-5; Docetaxel, in vivo distribution, liposomes, nude mice; Liposomes, docetaxel-loaded; Luteinizing hormone-releasing hormone analogues; Ovarian tumor targeting